A Review of Inconvertibility of Iran Nuclear Deal into an International Treaty - Mojtaba Mireh Gini; Maryam Sedaghat (Budapest International Research and Critics University, 2019)
International treaties become legal rules based on a social reality. The lawyers are convinced that JCPOA (Joint Comprehensive Plan of Action) is something novel and this has led them to identify the type of this agreement and to understand the scope of the requirements and obligations of the parties to the negotiations. The present study, based on analytical-descriptive method and by using the documents available in this field, has examined the differences and reasons for not converting Iran’s nuclear deal into an international treaty, and by understanding the nature of this contract, ultimately concludes that such an agreement, because it is more political in nature based on the distribution of power and the power equation in the international arena rather than having a legal nature, therefore it cannot be converted into an international treaty.